Retrospective analysis of HIV-associated lymphomas: insights from a single Romanian center over 15 years - Padurariu-Covit, Monica-Daniela; Chiscop, Iulia; Gutu, Cristian; Arbune, Anca-Adriana; Niculet, Elena; Arbune, Manuela (Frontiers in Oncology, 2025)
IntroductionLymphoma is a significant cause of mortality among people living with human immunodeficiency virus (PLWH). The objective of our study was to assess the characteristics of lymphomas in PLWH in a single center from the southeast of Romania.MethodsWe retrospectively analyzed the prevalence and clinical and demographic characteristics of patients with lymphoma associated with HIV/AIDS monitored over a period of 15 years. Kaplan–Meier analysis was used to estimate survival rates and evaluate the risk of mortality in lymphoma patients.ResultsAmong the 476 new cases of HIV/AIDS registered, 9 cases of lymphoma were identified, representing a prevalence of 1.89%. Overall mortality was 13.6%, with lymphoma contributing to 10.76% of HIV/AIDS-related deaths. The average age at lymphoma diagnosis was 37 years, with most patients being men and smokers with sexually transmitted HIV. Common coinfections included hepatitis B virus (HBV) and tuberculosis. Advanced-stage disease (Ann Arbor stage IV) and type B clinical symptoms were present in half of the cases. Oncological treatment was provided in 5 cases, achieving a survival rate of 30%.ConclusionsThe high mortality highlights the need for early diagnosis and an integrated therapeutic approach to improve the prognosis of patients with HIV-associated lymphomas.